MDDSVsim: An Integrated Traffic Simulation Platform for Autonomous Vehicle Research - Bouroche, Melanie; Clarke, Siobhan; Cahill, Vinny; O'Hara, Niall (My University, 2012)
Research and development in the field of intelligent transportation systems (ITS) can be costly in terms of both time and money. A significant initial and ongoing investment is often required in order to obtain a physical platform from which experimentation and results may be gained. Simulation of entities, their dynamics and interactions can provide an appropriate and cost effective method for the development of vehicular applications. When simulating traffic behaviour, it is modelled either at a microscopic level, where the individual characteristics and behaviours of each vehicle are reproduced, or at a macroscopic level where the traffic behaviour is aggregated and represented in terms of density, flow and speed. A difficulty with macroscopic simulation it that it often simplifies certain aspects of a scenario under investigation. Non-realistic vehicle dynamics, simplified communication models and idealistic localisation can all detract from the credibility of evaluations carried out. While microscopic simulation can alleviate these concerns, the computational resources required to simulate a large scale scenario, such as a highway, become prohibitive. This paper demonstrates that the integration of a number of simulation platforms can help alleviate the aforementioned concerns. Based on this premise we present MDDSVsim, the integration of (i) VISSIM - a microscopic simulation program for multi-modal traffic flow modelling, (ii) Microsoft Robotics Developer Studio (MRDS) - a robotics simulation platform, (iii) OPNET - a discrete event simulation engine and finally (iv) The World Model, a framework for building perception systems for robots and intelligent vehicles.
The International Workshop on Vehicular Traffic Management for Smart Cities (VTM 2012)
PUBLISHED
invited paper.
Dublin, Ireland
Keywords: Computer Science; Smart & Sustainable Planet